1987
DOI: 10.1016/0014-5793(87)81435-7
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic receptors regulate a voltage‐insensitive but Na+‐dependent calcium influx pathway in salivary acinar cells

Abstract: The calcium-sensitive fluorescent probe, quin 2, was employed to investigate the cholinergic receptor regulation of cytosolic free calcium concentration ([Ca2+],) in isolated rat submandibular acinar cells. Cholinergic receptor stimulation results in a marked and sustained elevation [Ca*+],. The major component of this response is shown to be due to activation of a calcium influx pathway. There is no evidence in K+-depolarized cells of any voltage-gated calcium influx. Acetylcholine failed to activate the calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 14 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…Recently, it was reported that activation of the Na+/H + exchanger by agonists (which increase intracellular Na--and reduce intracellular H + concentrations) was followed by an increase in [Ca2+]i (Grinstein & Goetz, 1985;Siffert & Akkerman, 1987). In addition, removal of extracellular Na § eliminated the sustained phase of the increase in [Ca2+]/induced by acetylcholine stimulation of salivary acinar cells (Morris, Fuller & Gallacher, 1987). However, the increase in [Ca2+]i following the stimulation of the Na § § exchanger was secondary to cytosolic alkalinization, rather than the increase in intracellular Na + concentration (Grinstein & Goetz, 1985;Siffert & Akkerman, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it was reported that activation of the Na+/H + exchanger by agonists (which increase intracellular Na--and reduce intracellular H + concentrations) was followed by an increase in [Ca2+]i (Grinstein & Goetz, 1985;Siffert & Akkerman, 1987). In addition, removal of extracellular Na § eliminated the sustained phase of the increase in [Ca2+]/induced by acetylcholine stimulation of salivary acinar cells (Morris, Fuller & Gallacher, 1987). However, the increase in [Ca2+]i following the stimulation of the Na § § exchanger was secondary to cytosolic alkalinization, rather than the increase in intracellular Na + concentration (Grinstein & Goetz, 1985;Siffert & Akkerman, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…We used amiloride at lower concentration (10 M) because it can inhibit not only ENaC but also NHEs at higher concentrations (Orlowski and Kandasamy, 1996;Praetorius et al, 2000). Furthermore, the Na ϩ -dependent Ca 2ϩ transport mechanism (presumably the Na ϩ /Ca 2ϩ exchanger) was shown to be functionally expressed in the rat submandibular gland Morris et al, 1987) and may be affected by amiloride. However, replacement of external Na ϩ with Li ϩ to inhibit Na ϩ /Ca 2ϩ exchanger activity (Blaustein and Santiago, 1977;Laskowski and Medler, 2009) failed to show any significant change in [Ca 2ϩ ] i in response to CCh, suggesting that it may be present in mouse submandibular gland, but it is not functionally important during muscarinic stimulation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of the human sweat gland indicate that only the first of these phases is inhibited by removal of external sodium (Bovell, Elder, Jenkinson & Wilson, 1989 b). The sweat gland therefore appears to differ from the extensively studied rat submandibular gland where secretagogue-evoked calcium entry, but not mobilization, appears to be sodium dependent Morris, Fuller & Gallacher, 1987;Bovell, Elder, Pediani & Wilson, 1989c).…”
Section: Introductionmentioning
confidence: 97%
“…The sweat gland therefore appears to differ from the extensively studied rat submandibular gland where secretagogue-evoked calcium entry, but not mobilization, appears to be sodium dependent Morris, Fuller & Gallacher, 1987;Bovell, Elder, Pediani & Wilson, 1989c).…”
Section: Introductionmentioning
confidence: 99%